2015
DOI: 10.1016/j.epsl.2015.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Diffusive over-hydration of olivine-hosted melt inclusions

Abstract: Editor: B. Marty Keywords: melt inclusion melt mixing diffusion water olivine IcelandThe pre-eruptive water content of magma is often estimated using crystal-hosted melt inclusions. However, olivine-hosted melt inclusions are prone to post-entrapment modification by H + diffusion as they re-equilibrate with their external environment. This effect is well established for the case of H + loss from olivine-hosted inclusions that have cooled slowly in degassed magma. Here we present evidence for the opposite effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 65 publications
4
45
0
Order By: Relevance
“…The apparent absence of H + diffusion may be attributed to minimal H 2 O concentration gradients between inclusions and the host magma during crystal residence, coupled with fast magma ascent prior to and during the 2014 eruption, which would severely limit the time for diffusion under an H 2 O gradient. During magma storage, the activity gradient between the melt inclusions and carrier melt was calculated at -0.07, which is comparable with values of ~0.04 that Hartley et al (2015) argued may have been too small to facilitate H + diffusion through olivine crystals. However, if diffusion occurred under these low activity gradients, calculated diffusive time scales range from 1 week to 5 months.…”
Section: Resultssupporting
confidence: 54%
“…The apparent absence of H + diffusion may be attributed to minimal H 2 O concentration gradients between inclusions and the host magma during crystal residence, coupled with fast magma ascent prior to and during the 2014 eruption, which would severely limit the time for diffusion under an H 2 O gradient. During magma storage, the activity gradient between the melt inclusions and carrier melt was calculated at -0.07, which is comparable with values of ~0.04 that Hartley et al (2015) argued may have been too small to facilitate H + diffusion through olivine crystals. However, if diffusion occurred under these low activity gradients, calculated diffusive time scales range from 1 week to 5 months.…”
Section: Resultssupporting
confidence: 54%
“…Whilst a number of studies have investigated the postentrapment behaviour of volatiles in olivine-hosted melt inclusions (e.g. Qin et al 1992;Portnyagin et al 2008;Bucholz et al 2013;Hartley et al 2015), volatile behaviour in plagioclase-hosted melt inclusions is less well understood. Whilst the high H 2 O content of melt inclusions precludes CO 2 loss during the final stages of eruption, it is not currently possible to evaluate how CO 2 may be transferred between inclusions and the external melt through plagioclase hosts, though diffusion along lattice defects and cleavage planes is likely to play a role (Viti and Frezzotti 2001;Kress and Ghiorso 2004).…”
Section: Magma Storage Depths and Barometric Inconsistenciesmentioning
confidence: 99%
“…Recent studies of both natural and experimental samples have shown that at magmatic temperatures, the H 2 O contents of crystal-hosted melt inclusions may be modified by several weight percent on timescales of hours to days by diffusive re-equilibration of H + between the melt inclusion and its external environment (e.g., Portnyagin et al 2008;Gaetani et al 2012;Bucholz et al 2013;Hartley et al 2015). Magmatic water contents at the time of melt inclusion trapping can be estimated using Ce as a proxy for H 2 O, if the undegassed H 2 O/Ce of the primary melt is known.…”
Section: H 2 O Ce and The Diffusive Re-equilibration Of H 2 O: Consmentioning
confidence: 99%